Perbandingan Pertanggungjawaban Pidana Direksi Di Indonesia Dan Belanda - Emiliya Febriyani (Nagari Law Review, 2021)
Directors are the most important organ in a company. But in practice, Directors often experience dilemmas in managing the company. On the one hand, Directors are required to make business decisions for the profit of the company. But on the other hand, if the loss causes a loss to the company, then the directors can be blamed and even held liable for criminal responsibility because it is deemed to have complied with the crime of corruption. That thing seems as if it has shown the gray area of law enforcement on directors' business decisions, which could be civil nature, but charged as criminal cases. For this reason, this paper compares the forms of criminal liability of Directors in Indonesia and the Netherlands. This paper uses a normative legal research method by using secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials relating to the comparison of criminal liability of Directors in Indonesia and the Netherlands which are analyzed using a comparative approach